(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article examines the image of the camel in the works of Chingiz Aitmatov typologically with Uzbek folklore. When the image of the camel is revealed, there is a convergence of mythological, religious views, and ethno-folkloristic concepts.